Factors influencing intentions on use of cash waqf as an aid in time of Covid-19 in Malaysia - Abdul Razak, Dzuljastri; Amin, Hanudin; Zuhaimi, Aidi Zuhaili (Zek Rokman Resources, 2021)
The COVID 19 pandemic has yielded an unprecedented crisis globally and people are still struggling for solutions to deal with the crisis. The effect is very broad-based be it on a social, economic, and healthy way of living. The purpose of this study is to investigate respondents' intention to use cash waqf as an aid in the time of COVID-19 in Malaysia. This is carried out by the analysis of the Theory of Reasoned Action (TRA) that demonstrates the relationship between attitudes and subjective norms within human action. It is mainly used to predict how individuals will behave based on their behaviours. A total of 418 respondents were collected using an individual and online survey. The result of the study indicated that attitude has a stronger influence than the subjective norm in respondents’ intentions to perform cash waqf. The results will benefit regulators and practitioners in planning the use of cash waqf as a product. Theoretically, this study has contributed to a new limited body of knowledge presently available on cash waqf, where the COVID-19 Pandemic crisis comes into play.